Cultural Values and Knowledge through Hofstede’s Framework: A Bibliometric and Bipartite Network Study of Cooperatives - Garcia-Aliaga, M. Isabel; Hernandez-Tamurejo, Alvaro; Ribeiro-Soriano, Domingo (Transformations In Business & Economics, 2025)
This study explores how cultural values, based on Hofstede’s dimensions, are applied to the study of cooperatives, identifying dominant themes, key academic contributions, and regional patterns in the literature. Understanding how cooperatives, as democratic and member-driven organisations, operate within different cultural contexts offers new insights into the intersection of culture, governance, and the social economy. A bibliometric analysis is conducted to classify, categorise, and identify relationships among academic publications on cooperatives and cultural values. The study employs VOSviewer to map intellectual structures, key thematic clusters, and regional trends. Additionally, a bipartite network co-occurrence analysis using Python is used to examine the intersection of Hofstede’s cultural dimensions, regional influences, and thematic keywords, thereby providing a structured framework for understanding cooperative governance. The results indicate that Hofstede’s framework can provide valuable insights into cooperative governance, as its dimensions align well with the democratic and member-driven nature of these organisations. Based on the results, the influence of cultural factors in cooperatives varies according to regional contexts and the specific purposes or industries in which they operate. This variability underscores the importance of considering local cultural nuances when evaluating cooperative practices. The study identifies key thematic areas to correctly explore culture on cooperatives based on Hofstede’s dimensions. The present study provides a systematic examination of the intersection between cultural dimensions and cooperatives, an approach to cooperatives culture study as it has been marginal so far. By mapping out the structure of the research area and analysing regional and keyword trends, this study contributes to a deeper understanding of how cultural values influence cooperative governance and decision-making across diverse socio-economic contexts proposing a research agenda from the perspective of Hofstede’s ideas.
Keywords: cooperatives; Hofstede; culture; bibliometric analysis; social economy